The Doctors of Democracy: Self-Image and Democratic Values of Participatory Practitioners - Dennis Friess; Nina Katharina Herff (Journal of Deliberative Democracy)
Against the backdrop of a perceived crisis of democracy, governments around the globe have extended citizens’ opportunities for public participation. Due to the increasing routinization of participatory processes, a vibrant participation industry has emerged where Professional Participation Practitioners (PPP) sell their services and knowledge to public clients. Despite the powerful role PPP play throughout the process of public participation, scholarly attention has been limited. This study provides seldom insides on PPP self-image and democratic value perceptions using an innovative Q-methodology design. Findings reveal similarities between PPP with regard to the commitment to strengthen democracy, providing transparent and fair participatory processes and raising citizens democratic competences. Further, PPP perceive their influential role within the participatory process but unanimously reject responsibility for final outcomes. Regarding difference among the surveyed PPP an explorative factor analysis suggests five distinguished types (Empowering Democracy Enhancer, Mediating Facilitator, Enlightening Contractor, Democratic Teacher, Agonistic Mediator). This typology sets the ground for further research on PPP who are likely to affect democratic practices not only nowadays but also in the future.